2020
DOI: 10.1080/22297928.2020.1785325
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Antimicrobial Activity and Molecular Docking of Pyrazole Bearing the Benzodiazepine Moiety

Abstract: Antibacterial assayMueller Hinton Broth dilution method (Becton Dickinson, USA) was used for the antibacterial assay of synthesized compounds. The strains used for antimicrobial activity of newly synthesized compounds were procured from the IMTECH, Chandigarh. The compounds (2a-t) were screened for their antibacterial activity in triplicate sets against these bacteria at different concentrations of 1000, 500, 250, and 200 μg/mL. The drugs which were found to be active in primary analysis were further diluted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…This site consists of ‐GCG‐ of the dodecamer [19] . The previous studies have shown that pyrazole derivatives could bind a protein or an enzyme as a target molecule with a range of −10.5 kcal/mol, [26] −9.486 kcal/mol, [27] −8.298 kcal/mol, [28] −6.00 kcal/mol [29] . It seems all the selected modes of poly(PDPPD) have shown a binding affinity in a range similar to previous studies binding area.…”
Section: Resultsmentioning
confidence: 99%
“…This site consists of ‐GCG‐ of the dodecamer [19] . The previous studies have shown that pyrazole derivatives could bind a protein or an enzyme as a target molecule with a range of −10.5 kcal/mol, [26] −9.486 kcal/mol, [27] −8.298 kcal/mol, [28] −6.00 kcal/mol [29] . It seems all the selected modes of poly(PDPPD) have shown a binding affinity in a range similar to previous studies binding area.…”
Section: Resultsmentioning
confidence: 99%
“…(3-(1,3-Diphenyl-1 H -pyrazol-4-yl)-1-arylprop-2-en-1-ones ( 3a – 3o ) were prepared according to the method as per the literature method. 39 …”
Section: Methodsmentioning
confidence: 99%
“…Using OPD(OPD) and a,b-unsaturated ketones. Desai et al 54 developed an efficient methodology for the synthesis of pyrazole-bearing BZDs (3) using OPD (1) and 3-(1,3-diphenyl-1H-pyrazol-4-yl)-1-phenylprop-2-en-1-ones (2) with piperidine and acetic acid as catalysts. The desired products were obtained in 8-10 h using a DMF solvent under reux conditions.…”
Section: 5-bzdsmentioning
confidence: 99%